2022
DOI: 10.1155/2022/7910566
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of C-Peptide and Diabetes Mellitus on Coronary Ectasia and Effect of Coronary Ectasia and C-Peptide on Long-Term Outcomes: A Retrospective Cohort Study

Abstract: Background. Coronary artery ectasia (CAE) is an entity frequently associated with atherosclerotic coronary artery disease (CAD) in clinical practice. Although it has common risk factors with atherosclerotic CAD in its development, the pathophysiology of CAE is not fully known and it is not seen in every CAD suggesting that different determinants may play a pivotal role in the development of CAD. This study aimed to reveal the impact of C-peptide and diabetes mellitus (DM) on CAE and the effect of C-peptide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Results indicated that higher C-peptide levels were independently associated with CAE, and both CAE and C-peptide emerged as independent predictors for major adverse cardiovascular events. 41 Furthermore, Toprak set al assessed the role of HbA1c/ C-peptide ratio (HCR) for high thrombus burden (HTB) and short-term mortality in ST-elevation myocardial infarction (STEMI) patients. HCR was found significantly higher in the HTB group and strongly correlated with short-term mortality, suggesting its potential as a prognostic marker in STEMI patients.…”
mentioning
confidence: 99%
“…Results indicated that higher C-peptide levels were independently associated with CAE, and both CAE and C-peptide emerged as independent predictors for major adverse cardiovascular events. 41 Furthermore, Toprak set al assessed the role of HbA1c/ C-peptide ratio (HCR) for high thrombus burden (HTB) and short-term mortality in ST-elevation myocardial infarction (STEMI) patients. HCR was found significantly higher in the HTB group and strongly correlated with short-term mortality, suggesting its potential as a prognostic marker in STEMI patients.…”
mentioning
confidence: 99%
“…A ectasia isolada da artéria coronária (EIAC) é frequentemente encontrada na prática clínica com métodos de imagem invasivos crescentes, e nosso conhecimento sobre sua etiologia, prognóstico e abordagens de tratamento está aumentando diariamente. 1 , 2 Lemos com grande interesse o recente estudo retrospectivo de Dindas et al, 3 que trata da relação entre o Índice de Inflamação Imunológica Sistêmica (IIS) e EIAC. 3 Foi sugerido que neutrófilos, plaquetas e linfócitos IIS coletados em uma única fração podem ser um bom indicador de inflamação e resposta imune.…”
unclassified
“…Isolated coronary artery ectasia (ICAE) is frequently encountered in clinical practice with increasing invasive imaging methods, and our knowledge about its etiology, prognosis, and treatment approaches is increasing daily. 1 , 2 We read with great interest the recent retrospective study of Dindas et al, 3 which deals with the relationship between the Systemic Immune Inflammation Index (SII) and ICAE. 3 It has been suggested that SII neutrophils, platelets, and lymphocytes collected in a single fraction may be a good indicator of inflammation and immune response.…”
mentioning
confidence: 99%